Crowdsourcing Water Quality Data : A Conceptual Framework - World Bank (World Bank, Washington, DC, 2016)
Using mobile phone technologies coupled with water quality testing, there is great opportunity to increase the awareness of water quality throughout rural and urban communities in developing countries. Whether the focus is on empowering citizens with information about the quality of water they use in daily life or providing scientific data to water managers to help them deliver safe water to the citizens, the integration of citizen science, crowdsourcing, and innovative technologies has the potential to create positive and lasting change. The methodology presented herein combines empowerment of the public through participation in the scientific process (citizen science) with modern technologies to collect, gather, and disseminate data (crowdsourcing). By employing a crowdsourcing approach with innovative technologies, there is potential to harness large amounts of data in areas previously considered either too remote or costly to access. The purpose of this conceptual framework is to outline the considerations and activities to be undertaken for a successful water quality monitoring project using citizen science and crowdsourcing. Specifically included in the framework are: (1) the research question to be answered through the project; (2) the theory of change that will lead to desired outcomes; (3) project design considerations to promote a successful pilot; and (4) the methodology outlining implementation steps.